Computer Assisted Interpreter Training for Students Who Are Not Foreign Language Majors - Cheng, Sheng-jie (Instytut Językoznawstwa Wydział Neofilologii, UAM, 2010)
The aim of the existing case study was to investigate the implications of applying computers to teaching interpreting to students who were not foreign language majors. Some researchers argued that interpreting courses are very difficult, so they should be offered to qualified post-graduate students instead of undergraduate students. However, most undergraduate programs in Taiwan offer interpretation courses. In addition, in China two-semester interpreter training courses have even been offered to most undergraduate students who were not foreign language majors. Furthermore, computers have been widely used in interpreter training, but no research has been available that investigated how to apply computer assisted interpreter training (CAIT) to teaching interpreting to students who are not foreign language majors. Qualitative research methods have been used to collect and analyze the data to complete the report in this study. Participants consisted of the author and the 18 students, who were not foreign language majors, taking a computer assisted interpreter training course that the author offered in a university in Taipei, Taiwan, in 2009. The results of the study indicated that CAIT may be developed into IM (the interpretation method) of foreign language teaching to teach students who are not foreign language majors.

本個案研究旨在探討如何運用電腦輔助口譯教學於教授外系(非外文系)的學生。有些專家主張口譯課很困難所以只能在研究所開設給有資格的學生學習，而不應該開給大學部的學生。但是在台灣大部份的大學部都有開口譯課。在中國甚至大部份的外系(非外文系)都在開為期兩個學期的口譯課。電腦廣泛的運用於口譯教學，但是卻很少研究探討如何運用電腦於外系的口譯教學。本研究採用質的方式收集與分析資料完成本論文，實驗參與者包括筆者與選修筆者2009年在台北一所大學開設的電腦輔助口譯課的18位外系的學生。本研究結果顯示電腦輔助口譯教學可以發展成為獨樹一格的教學法，以透過教授口譯訓練技巧的方式教外系學生外文。
Wspomagane komputerowo szkolenie tłumaczy ustnych dla studentów kierunków niefilologicznych
非外文系電腦輔助口譯教學